How do small nations cooperate? An action research framework for Wales and the Basque Country - Igor Calzada (Regional Studies, Regional Science)
Against the backdrop of the Memorandum of Understanding (MoU) signed between the Welsh and Basque Governments in 2018, this article introduces a multiscalar and transdisciplinary social sciences action research framework that emerged from a workshop held in May 2023. The workshop engaged stakeholders from both sides and is part of the broader ongoing project. This project seeks to address the main research question, ‘How do small nations cooperate?’ through the exploration of transregional cooperation and mutual learning between Wales and the Basque Country. The structure of the article is as follows: First, it commences with an introduction defining ‘small nations’, presenting the main research question, articulating two related aims, outlining three primary methodological goals and providing a broad context for these two small nations within the framework of their MoU. Second, following a brief description of each small nation, the article concurrently develops the action research methodological framework while analysing findings stemming from workshop discussions between stakeholders of Wales and the Basque Country. They addressed three intertwined territorial scale challenges: Macro, examined through devolution and fiscal federalism perspectives; Meso, explored through social innovations in urban spaces in Cardiff (SPARK) and Bilbao (ASFabrik); and Micro, investigated through grassroots innovations. Finally, the article concludes with an action research and policy agenda. It suggests one operational research question per territorial scale as the conclusion of this article, offering a response to the main research question. The conclusion acknowledges limitations and outlines future research and policy pathways for this ongoing project.